A compact two-phase twisted string actuation system: Modeling and validation. (July 2016) - Tavakoli, Mahmoud; Batista, Rafael; Neto, Pedro
Abstract: In this paper, we propose a compact twisted string actuation system that achieves a high contraction percentage (81%) on two phases: multi string twist and overtwist. This type of system can be used in many robotic applications, such as robotic hands and exoskeletons. The overtwist phase enables the development of more compact actuators based on the twisted string systems. Furthermore, by analyzing the previously developed mathematical models, we found out that a constant radius model should be applied for the overtwisting phase. Moreover, we propose an improvement of an existing model for prediction of the radius of the multi string system after they twist around each other. This model helps to better estimate the bundle diameter which results in a more precise mathematical model for multi string systems. The model was validated by performing experiments with 2, 4, 6 and 8 string systems. Finally, we performed extensive life cycle tests with different loads and contractions to find out the expected life of the system. Abstract :